Factors That Affect Back Pain In Second And Third Trimester Pregnant Women - Triwik Sri Mulati; Tri Wahyuni; Kuswati Kuswati; Dewi Susilowati (Jurnal Kebidanan dan Kesehatan Tradisional, 2022)
Background: Back pain in pregnant women in the 2nd and 3rd trimesters, if not treated immediately, will greatly disturb the comfort of pregnant women and can cause complications such as moderate to severe anxiety due to pregnant women not being able to adapt to their back pain. Several factors are associated with the occurrence of back pain in pregnant women. This study aims to prove the factors that affect back pain in second and third trimester pregnant women. Methods: This research was a cross sectional design. The sample was 30 pregnant women in the 2nd and 3rd trimesters experiencing back pain determined by using the total population sampling technique with the following inclusion and exclusion criteria. Back pain felt by pregnant women was stated in filling out a questionnaire with a pain instrument, namely the Numeric Rating Scale. The data were analyzed by statistical Odds Ratio Test. Results: The result of data analysis between pregnancy back pain with several factors are as follows: the OR value of mother age factor was 0.464. The OR value of gestational age factor was 0.571. The occupation’s OR value was 0.762. The parity’s OR value was 0.242. The religion’s OR value was 0.464. The OR value of gender was 1.000. The OR value of history of lifting heavy objects was 1.833. The OR value of history of excessive bending was 13.000. The yoga exercise’s OR value was 0.143. Conclusion: History of excessive bending has the greatest risk of back pain in pregnant women.